Morphostructural and immunohistochemical study on the role of metallothionein in the detoxification of heavy metals in Apis mellifera L., 1758. Issue 11 (22nd August 2017) - Salvaggio, Antonio; Pecoraro, Roberta; Scalisi, Elena Maria; Tibullo, Daniele; Lombardo, Bianca Maria; Messina, Giuseppina; Loreto, Francesco; Copat, Chiara; Ferrante, Margherita; Avola, Roberto; D'amante, Giusi; Genovese, Claudia; et al.
Abstract: Honey is a valuable food produced by bees from sugary substances that they gather in nature. The transformation the nectar into honey, by bees, is long and complex. Except for honey, where heavy metals are absent or are found only in traces, the bees and their products have always been considered excellent biomarkers of such contaminants. We have assumed that the absence of heavy metals in honey is due to the presence of a detoxification system in the digestive system of bees, which involves metallothioneins, proteins that have a role in the homeostatic control of essential and non‐essential metals. We have placed the beehives in three different zones: industrial, urban and rural. Investigations were carried out with ICP‐MS method for the detection of heavy metals in the guts of honey bees and honey. The metallothioneins have been identified by Immunohistochemical and Western‐blotting analisys. The investigations have shown the presence of heavy metals only in bees guts but not in honey, while the presence of metallothionein has been highlighted only in epithelium of the honey sac, demonstrating the existence of an efficient system of detoxification of heavy metals. Abstract : In honey bees the detoxification system is primarily based on induction of Metallothioneins Metallothionein‐immunopositive cells only in the honey sac.